A Critical Study of Hermeneutics in the Interpretation of the Qur'an Regarding Educational Verses - Soni Harsono; Ahmad Syagif HM; Junaidin Junaidin (STIT Sunan Giri Bima, 2025)
This study aims to critically examine the application of the hermeneutic approach in interpreting the verses of the Qur'an relating to education. In the modern context, hermeneutics is certainly seen as an alternative method of interpretation that seeks to connect the text, context, and subjectivity of the reader in order to gain a more relevant understanding of the educational values in the Qur'an. The research method used is descriptive qualitative based on literature studies as a step to visualize and analyze related to the study in this study to trace the history of hermeneutics, variants in hermeneutics, figures of Qur'anic hermeneutics in interpreting educational verses, and how the polemics that occur between groups that are pro-hermeneutics and against it. The results of the research that can be presented in this study are that the hermeneutic method can contribute to enriching the discourse of interpretation so that it can open space for a more dynamic and contextual understanding of educational verses such as Qs. Al-Alaq verses 1-5, Qs. Al-Mujadalah verse 11, Qs. Luqman verse 13, Qs. Al-Ahzab verse 21, and Qs. An-Nahl verse 125. However, in this case, caution is needed to maintain the integrity of the meaning contained in the text itself, especially the text of the Qur'an. With this research, the author certainly hopes it will be a valuable contribution as an interpretation methodology that is appropriate to the challenges of the future.